Cost-Effective Cloud Edge Traffic Engineering with CASCARA - Singh, Rachee; Agarwal, Sharad; Calder, Matt; Bahl, Victor (USENIX NSDI, 2021)
Inter-domain bandwidth costs comprise a significant amount of the operating expenditure of cloud providers, but have received little attention in research and practice. Traffic engineering systems at the cloud edge must strike a fine balance between minimizing costs and maintaining the latency expected by clients. The nature of this tradeoff is complex due to non-linear pricing schemes prevalent in the market for inter-domain bandwidth. We quantify this tradeoff and uncover several key insights from the link-utilization between a large cloud provider and Internet service providers. Based on these insights, we propose CASCARA, a cloud edge traffic engineering framework to optimize inter-domain bandwidth allocations with non-linear pricing schemes. CASCARA exploits the abundance of latency-equivalent peer links on the cloud edge to minimize costs without impacting latency significantly. Extensive evaluation on production traffic demands of a commercial cloud provider shows that CASCARA saves 11–50% in bandwidth costs per cloud PoP, while bounding the increase in client latency by 3 milliseconds.